A DEMETER-like DNA demethylase protein governs tomato fruit ripening - Liu, Rui E.; How-Kit, Alexandre; Stammitti, Linda; Teyssier, Emeline; Rolin, Dominique; Bertrand, Anne; Halle, Stefanie; Liu, Mingchun; Kong, Junhua; Wu, Chaoqun; Degraeve-Guibault, Charlotte; Chapman, Natalie; et al. (National Academy of Sciences, 2015)
In plants, genomic DNA methylation which contributes to development and stress responses can be actively removed by DEMETER-like DNA demethylases (DML). Indeed, in Arabidopsis DMLs are important for maternal imprinting and endosperm demethylation, but only few studies demonstrate the developmental roles of active DNA demethylation conclusively in this plant. Here we show a direct cause and effect relationship between active DNA demethylation mainly mediated by the tomato DML, SlDML2, and fruit ripening; an important developmental process unique to plants. RNAi SlDML2 knock-down results in ripening inhibition via hypermethylation and repression of the expression of genes encoding ripening transcription factors and rate-limiting enzymes of key biochemical processes such as carotenoid synthesis. Our data demonstrate that active DNA demethylation is central to the control of ripening in tomato